Lignins from sugarcane bagasse: Renewable source of nanoparticles as Pickering emulsions stabilizers for bioactive compounds encapsulation - Bertolo, Mirella R.V.; Brenelli de Paiva, Lívia B.; Nascimento, Viviane M.; Gandin, Cesar A. [UNESP]; Neto, Mario O. [UNESP]; Driemeier, Carlos E.; Rabelo, Sarita C. [UNESP] (Elsevier, 2019)
Lignin nanoparticles has gained interest in recent years in a wide range of applications due to its unique properties compared to the microsized material. Furthermore, lignin is obtained from lignocellulosic biomass processing and it is still considered a poorly exploited macromolecule due to the heterogeneous nature and low solubility in aqueous medium. This study focus on the comparison between two ways environmentally friendly of obtaining colloidal lignin nanoparticles (LNPs), considering minimal processing steps and employing lignins derived from two sugarcane bagasse pretreatments (alkaline and organosolv). Raw lignins and LNPs were characterized by different techniques such as scanning electron microscopy (SEM), zeta potential, dynamic light scattering (DLS), small-angle X-ray scattering (SAXS) and antioxidant assay in order to evaluate the changes in its morphological, chemical and antioxidant properties. The results showed the formation of spherical-like nanoparticles which sizes were determined by the synthesis method. LNPs obtained from alkaline lignin showed an average diameter varying from 115 to 300 nm, while LNPs obtained from organosolv lignin ranged from 270 to 680 nm, as determined by DLS. All LNPs in aqueous suspension had a zeta potential ranging from −25 to −35 mV, which is considered stable for colloidal systems. The thermal stability properties of micro to nanosized lignins were preserved. The antioxidant capacity against the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical was improved for alkaline-LNPs compared to the raw lignin (IC30 = 12 and 9.9 μg mL−1, respectively), and worsened for organosolv-LNPs compared to the raw lignin (IC30 = 11.4 and 15 μg mL−1, respectively). Furthermore, LNPs were tested as stabilizing agents of Pickering emulsions, used as encapsulation agents of curcumin, a polyphenol with a wide range of pharmacological applications. Organosolv-LNPs were seen to be the most efficient stabilizer, retaining 73% of curcumin in its encapsulated form after 96 h. Therefore, this study demonstrated the potential of nanostructured lignins for bio-based field, and also highlights the influence factors for the choice of methodology and raw lignins over the properties resulted of LNPs.
Keywords: Encapsulating agent; Lignin nanoparticles; Pickering emulsion; Sugarcane bagasse